Wise old woman (The) - Uchida, Yoshiko (New York : Margaret K McElderly Books, 1994)
An old woman demonstrates the value of her age when she solves a warload's three riddles and saves her village from destruction.
Keywords: Folklore -- Japan; Old age -- Folklore